2011
DOI: 10.1177/1363461511408493
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between acculturation factors and symptoms of depression: A cross-sectional study with immigrants living in Athens

Abstract: The process of acculturation observed in immigrants is part of an adjustment to the values and norms of a new society, and possibly the loss of norms of the society of origin. Acculturation has been linked to stress-related psychological disorders such as depression. The present study investigates the relationship between three acculturation domains (everyday life behaviors, wishful orientation/nostos, and ethnic identity) and symptoms of depression in a sample of foreign immigrants living in Athens, Greece. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…Tinghog et al (2007) and Missinne and Bracke (2012) demonstrated that the prevalence of mental illnesses among migrants in different European countries depends on their socio-economic situation. Studies about the effect of length of stay in the host country are inconsistent (Gonidakis et al, 2011;Breslau and Chang, 2006). Further, the rate of dysphoric disorders differs between migrants with different ethnic background within the same host country (De Wit et al, 2008;Levecque et al, 2007;Weich et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Tinghog et al (2007) and Missinne and Bracke (2012) demonstrated that the prevalence of mental illnesses among migrants in different European countries depends on their socio-economic situation. Studies about the effect of length of stay in the host country are inconsistent (Gonidakis et al, 2011;Breslau and Chang, 2006). Further, the rate of dysphoric disorders differs between migrants with different ethnic background within the same host country (De Wit et al, 2008;Levecque et al, 2007;Weich et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…First, acculturative stress was described as the divergence a racial/ethnic minority person experiences when exposed to a dissimilar culture (35). Such as acculturative stress is linked to mental disorders, especially depression (36). …”
Section: Introductionmentioning
confidence: 99%
“…anxiety, depression). Gonidakis et al 4 found that more assimilation strategies are related to lower levels of depression in the Attica region. Furthermore, as mentioned before, according to Prapas and Mavreas, 5 less assimilated immigrants in Attica experience more cultural dissonance and conflict with host culture, especially in societies with assimilation pressures toward immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, Greece has become one of the "recipient" countries of immigrants from the Balkans and several Asian countries. 1 Even though most findings suggest that immigrants in Greece prefer integration or assimilation over separation [2][3][4] which are related to lower levels of depression, the role of the acculturation attitudes of Indian immigrants in Greece and the social support they receive in anxiety and depression feelings has never been studied before. Less assimilated immigrants seem to experience in Attica more cultural dissonance and conflict with host culture, 5 but a crucial question remains: if it is feasible and adaptive for immigrants with many cultural differences from Greeks to become assimilated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation